2018
DOI: 10.1016/j.heares.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in signal and sensory precision both constrain auditory acuity at high frequencies

Abstract: Sensory performance is constrained by the information in the stimulus and the precision of the involved sensory system(s). Auditory spatial acuity is robust across a broad range of sound frequencies and source locations, but declines at eccentric lateral angles. The basis of such variation is not fully understood. Low-frequency auditory spatial acuity is mediated by sensitivity to interaural time difference (ITD) cues. While low-frequency spatial acuity varies across azimuth and some physiological models predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…Different auditory cue statistics have been examined in previous studies, as well as their predictive accuracy of human auditory spatial discriminability. Higher ITDrc in the midline supports the better spatial discrimination observed in frontal locations ( Mills and localization, 1972 ; Gelfand, 2016 ; Brown et al, 2018 ). Consistent with previous reports ( Woodworth, 1938 ; Feddersen et al, 1957 ; Gelfand, 2016 ), we found that ITDrc was higher in the midline for most frequencies.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Different auditory cue statistics have been examined in previous studies, as well as their predictive accuracy of human auditory spatial discriminability. Higher ITDrc in the midline supports the better spatial discrimination observed in frontal locations ( Mills and localization, 1972 ; Gelfand, 2016 ; Brown et al, 2018 ). Consistent with previous reports ( Woodworth, 1938 ; Feddersen et al, 1957 ; Gelfand, 2016 ), we found that ITDrc was higher in the midline for most frequencies.…”
Section: Resultsmentioning
confidence: 76%
“…Different auditory cue statistics have been examined in previous studies, as well as their predictive accuracy of human auditory spatial discriminability. Higher ITDrc in the midline supports the better spatial discrimination observed in frontal locations (Mills et al 1972;Gelfand 2016;Brown et. al, 2018).…”
Section: B Cmentioning
confidence: 70%
See 1 more Smart Citation
“…ILDs have been shown to become non-monotonic with increasing azimuth and thus ILDs possibly effect the localisation performance (e.g. [61]). In contrast to mammals, barn owls exploit ITD and ILD cues differently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the multiplicative combination of ITD and ILD cues demonstrated in the barn owl's midbrain neurons , an optimal operation for integration of statistically independent cues (Fischer and Peña, 2017), was first proposed for human binaural cue integration (Stern and Colburn, 1978). Furthermore, recent human studies indicate that ILD cue statistics explain highfrequency spatial acuity in humans (Brown et al, 2018). While the population vector may not describe behavior in all species, other implementations of optimal inference may be used (Day and Delgutte, 2013;Goodman et al, 2013).…”
Section: Functional Role Of Frequency-dependent Itd Tuning: Integrating Natural Statistics Into the Space Map Readoutmentioning
confidence: 99%